Effects of a single mental chronometry training session in subacute stroke patients - a randomized controlled trial - Joachim Liepert; Jana Stürner; Imke Büsching; Aida Sehle; Mircea A. Schoenfeld (BMC, 2020)
Abstract Background Motor imagery training might be helpful in stroke rehabilitation. This study explored if a single session of motor imagery (MI) training induces performance changes in mental chronometry (MC), motor execution, or changes of motor excitability. Methods Subacute stroke patients (n = 33) participated in two training sessions. The order was randomized. One training consisted of a mental chronometry task, the other training was a hand identification task, each lasting 30 min. Before and after the training session, the Box and Block Test (BBT) was fully executed and also performed as a mental version which served as a measure of MC. A subgroup analysis based on the presence of sensory deficits was performed. Patients were allocated to three groups (no sensory deficits, moderate sensory deficits, severe sensory deficits). Motor excitability was measured by transcranial magnetic stimulation (TMS) pre and post training. Amplitudes of motor evoked potentials at rest and during pre-innervation as well as the duration of cortical silent period were measured in the affected and the non-affected hand. Results Pre-post differences of MC showed an improved MC after the MI training, whereas MC was worse after the hand identification training. Motor execution of the BBT was significantly improved after mental chronometry training but not after hand identification task training. Patients with severe sensory deficits performed significantly inferior in BBT execution and MC abilities prior to the training session compared to patients without sensory deficits or with moderate sensory deficits. However, pre-post differences of MC were similar in the 3 groups. TMS results were not different between pre and post training but showed significant differences between affected and unaffected side. Conclusion Even a single training session can modulate MC abilities and BBT motor execution in a task-specific way. Severe sensory deficits are associated with poorer motor performance and poorer MC ability, but do not have a negative impact on training-associated changes of mental chronometry. Studies with longer treatment periods should explore if the observed changes can further be expanded. Trial registration DRKS, DRKS00020355 , registered March 9th, 2020, retrospectively registered